2008
DOI: 10.2109/jcersj2.116.632
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electric properties of lead-free (Bi0.5Na0.5)TiO3-Ba(Zr0.04Ti0.96)O3 ceramics near the morphotropic phase boundary

Abstract: Extending the investigations on Bi-based solid solution for lead-free piezoelectric ceramics, this paper consider the complex solid-solution system (1-x)(Bi0.5Na0.5)TiO3-xBa(Zr0.04Ti0.96)O3 [(1-x)BNT-xBZT] for x < 0.12. High density polycrystalline ceramics were fabricated using conventional solid-state processing methods. These ceramics are then taken for structure and properties measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…According to the author's previous report, 9) the MPB of (1-x)NBT-xBZT system ceramic lies in the composition range of 0.05 ≤ x ≤ 0.07 at room temperature, where hexagonal and tetragonal phases coexist. The materials with perovskite structure are hexagonal phase at x ≤ 0.05 and become tetragonal phase at x ≥ 0.07.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the author's previous report, 9) the MPB of (1-x)NBT-xBZT system ceramic lies in the composition range of 0.05 ≤ x ≤ 0.07 at room temperature, where hexagonal and tetragonal phases coexist. The materials with perovskite structure are hexagonal phase at x ≤ 0.05 and become tetragonal phase at x ≥ 0.07.…”
Section: Resultsmentioning
confidence: 96%
“…The author 9) previously reported that 0.95(Na0.5Bi0.5)TiO3-0.05Ba(Zr0.04Ti0.96)O3 ceramics near the MPB has a good planar coupling factor (kp = 0.34). The author 9) reported that 0.99(Na0.5Bi0.5)TiO3-0.01Ba(Zr0.04Ti0.96)O3 ceramics exhibit a large anisotropy in the electromechanical coupling factor kt/kp (kt = 0.51, kp = 0.14) for high frequency electromechanical transducer applications. The comparison of properties of (Na0.5Bi0.5)TiO3 ceramics based on the previous reports of various groups are demonstrated in Table 1.…”
Section: +mentioning
confidence: 99%
“…Perovskite structure (Bi 1/2 Na 1/2 )TiO 3 [abbreviated as BNT] ceramics are considered as one of the candidates for lead-free piezoelectric ceramics because of its high ferroelectric properties and high Curie temperature (Tc = 320 o C). Some modifications of BNT ceramics have proved to be helpful by forming solid solution with other perovskite oxides [10][11]. Bi 0.5 (Na 0.93 K 0.07 ) 0.5 TiO 3 is well-known lead-free piezoelectric materials, which has a rhombohedral symmetry at room temperature and show better piezoelectric response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore BNT-based solid solution was studied to improve piezoelectric properties. Some modifications of BNT ceramic have proved to be helpful by forming solid solution with other perovskite oxides, [1][2][3][4][5][6][7] [4] (Bi 0.5 K 0.5 )TiO 3 , [5] (Sr 0.5 Ca 0.5 )TiO 3 , [6] and Ba(Ti 0.96 Zr 0.04 )TiO 3 [7] etc. A comparison of the properties of BNT ceramic based on the previous reports of various groups is shown in Table I.…”
Section: Introductionmentioning
confidence: 99%